Handedness preference and switching of peptide helices. Part I: Helices based on protein amino acids1. (23rd April 2014) - Zotti, Marta De; Formaggio, Fernando; Crisma, Marco; Peggion, Cristina; Moretto, Alessandro; Toniolo, Claudio
<x xml:space="preserve">Abstract</x> In this article, we review the relevant results obtained during almost 60 years of research on a specific aspect of stereochemistry, namely handedness preference and switches between right‐handed and left‐handed helical peptide structures generated by protein amino acids or appropriately designed, side‐chain modified analogs. In particular, we present and discuss here experimental and theoretical data on three categories of those screw‐sense issues: (i) right‐handed/left‐handed α‐helix transitions underwent by peptides rich in Asp, specific Asp β‐esters, and Asn; (ii) comparison of the preferred conformations adopted by helical host–guest peptide series, each characterized by an amino acid residue (e.g. Ile or its diastereomer aIle) endowed with two chiral centers in its chemical structure; and (iii) right‐handed (type I)/left‐handed (type II) poly‐(Pro)n helix transitions monitored for peptides rich in Pro itself or its analogs with a pyrrolidine ring substitution, particularly at the biologically important position 4. The unique modular and chiral properties of peptides, combined with their relatively easy synthesis, the chance to shape them into the desired conformation, and the enormous chemical diversity of their coded and non‐coded α‐amino acid building blocks, offer a huge opportunity to structural chemists for applications to bioscience and nanoscience problems. Copyright © 2014 European Peptide Society and John Wiley & Sons, Ltd.